Structuring Poverty in the Windy City : Autonomy, Virtue, and Isolation in Post-Fire Chicago - Black, Joel E. (University Press of Kansas, 2019)
"By digging through local newspapers, magazines, city reports, legal decisions, and archival materials, Joel E. Black tells the stories of the "tramps," sex workers, and migrants who found themselves caught within structures of poverty--the web of theories, policies, institutions, and practices that shaped a social order identifying who was poor and thus at the mercy of those who, in an effort to rebuild Chicago, claimed authority over their existence and compelled them to conform. Structuring Poverty looks at how the forces of institutional poverty operated on the ground in Progressive Era Chicago, and how these structures set the stage for similar efforts in the New Deal"--